2005
DOI: 10.1542/peds.2004-2697
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cardiac Rehabilitation on the Exercise Function of Children With Serious Congenital Heart Disease

Abstract: Objectives. The exercise capacity of children with congenital heart disease (CHD) is often depressed. This depression is thought to be attributable to (1) residual hemodynamic defects and (2) deconditioning secondary to physical inactivity. We hypothesized that this latter component would be ameliorated by a formal cardiac rehabilitation program designed specifically for children. The objective of this study was to characterize the effect of a cardiac rehabilitation program on the exercise performance of child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
120
2
13

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 171 publications
(143 citation statements)
references
References 38 publications
1
120
2
13
Order By: Relevance
“…On completion of a variety of training programs, peak Vȯ 2 has been reported to increase 7% to 21% over baseline values. [586][587][588][589] Most of the improvement appears to be attributable to an increase in the oxygen pulse at peak exercise. 589 In one study, the short-term improvements were sustained 6 to 9 months after the termination of the rehabilitation program (1 year after the prerehabilitation study) and were associated with improvements in lifestyle, perceived exercise function, self-esteem, and emotional state.…”
Section: Exercise Training In Padmentioning
confidence: 99%
See 1 more Smart Citation
“…On completion of a variety of training programs, peak Vȯ 2 has been reported to increase 7% to 21% over baseline values. [586][587][588][589] Most of the improvement appears to be attributable to an increase in the oxygen pulse at peak exercise. 589 In one study, the short-term improvements were sustained 6 to 9 months after the termination of the rehabilitation program (1 year after the prerehabilitation study) and were associated with improvements in lifestyle, perceived exercise function, self-esteem, and emotional state.…”
Section: Exercise Training In Padmentioning
confidence: 99%
“…[586][587][588][589] Most of the improvement appears to be attributable to an increase in the oxygen pulse at peak exercise. 589 In one study, the short-term improvements were sustained 6 to 9 months after the termination of the rehabilitation program (1 year after the prerehabilitation study) and were associated with improvements in lifestyle, perceived exercise function, self-esteem, and emotional state. 590 Improvements in exercise function and other areas were not observed in a control group, composed of 18 children with similar diagnoses, observed over the same time period.…”
Section: Exercise Training In Padmentioning
confidence: 99%
“…More recently, Rhodes et al 80 reported that, in a study of 16 children with serious CHD, a 12-week rehabilitation program was associated with a 17% increase in peak V O 2 . Improvements in the V O 2 at the VAT were even more substantial.…”
Section: Cardiac Rehabilitation For Childrenmentioning
confidence: 99%
“…80 However, data on the optimal design of pediatric cardiac rehabilitation programs do not exist, and further investigations are needed to elucidate the most effective rehabilitation strategies for children with CHD. Furthermore, reliance on a facility-based rehabilitation program is, for many patients, impractical, and the costs of these programs are not covered reliably by most third-party payers.…”
Section: Cardiac Rehabilitation For Childrenmentioning
confidence: 99%
“…The most wide-scale studies of physical loads' influence in cardio-rehabilitation programs for persons with CHD were made by J. Rhodes [26][27][28] -increase of peak VO 2 and maximal load for long period; P. E. Longmuir [20,21] -long term improvement of physical fitness indicators; L. M. Bradley [10] -improvement of peak VO 2 and endurance; I. C. Balfour [8] -improvement of peak VO 2 ; B. Goldberg [16] -improvement of maximal power and workability, influence on peak VO 2 was absent; H. D. Ruttenberg [29], P. M. Fredriksen [13] -improvement of endurance, influence on peak VO 2 was absent.…”
mentioning
confidence: 99%